Isolated Streptococcus intermedius pulmonary nodules. (2017) - Catalya, Stephen; Komal, Bushra; Tulpule, Sunil; Raoof, Nazar; Sen, Shuvendu
Highlights: S. intermedius infections can have extended hospital stays, but did not occur here. Abscess/empyema formation, typical in S. intermedius infection, did not occur here. A unique demographic of S. intermedius infection is shown, compared to literature. Abstract: Streptococcus intermedius, a member of the Streptococcal anginosus group of alpha-hemolytic streptococci, remains a notable infectious agent causing necrotizing pneumonia and abscesses. We report a case of a young male with pulmonary nodules found to have Streptococcus intermedius and no other underlying hepatic or dental history who was treated with ceftriaxone and avoided surgical intervention. A review of the literature reveals cases that are typically treated with a combined surgical and medical approach. These same cases often involve middle aged to elderly individuals who have a past history of tobacco use, alcoholic liver cirrhosis and/or poor dentition. This case stands out given the patient's atypical presentation.